Analisa Tebal Lapis Perkerasan Jalan Tgh. Faesal Menggunakan Metode Bina Marga 2017 dan AASHTO 1993 - Pratama, Khendy Marsa Duta; Wahyuningsih, Titik; Efendy, Anwar (LPPM Universitas Mataram, 2025)
Roads have an important role for society, especially in economic growth and industrial development in an area. Based on BPS NTB data in 2023, the length of the Mataram City road is 460 km, where one of the roads in Mataram City, namely TGH.Faesal road, is a connecting road between Mataram City and West Lombok Regency, which can be interpreted as the main road entering Mataram City. so that the condition of the TGH.Faesal road must continue to be analyzed or reviewed regularly so that the condition of the TGH.Faesal road continues to be in good condition. This research uses secondary data obtained from the National Road Planning and Supervision of West Nusa Tenggara Province (P2JN NTB). the methods used are the Bina Marga 2017 and AASHTO 1993 methods. The analysis was carried out to determine the design comparison of each method. The Bina Marga 2017 method obtained the thickness of the actual load pavement layer and normal load, namely the surface layer of 17.5 cm, and the foundation layer of 30 cm. The AASHTO 1993 method obtained the thickness of the pavement layer, namely the surface layer of 18 cm, and the foundation layer of 52 cm.